Dynamics and Challenges of Legal Regulation concerning Human Smuggling with Refugee Objects in Indonesia - Kukuh Kharisma, Lalu; Susilowati, Tri; Tohari, Mohamad (Politeknik Siber Cerdika Internasional, 2024)
This research discusses the dynamics and challenges in legal regulation related to human smuggling, focusing on refugees in Indonesia. Despite Indonesia being a significant transit country for refugees, the existing legal framework, particularly Law No. 6 of 2011 on Immigration, does not specifically regulate the status and protection of refugees. Consequently, refugees are often viewed as illegal immigrants, leading to human rights violations and legal uncertainty. The first subsection analyzes how dynamic legal regulations interact with the challenges faced in the context of human smuggling. It further explores necessary efforts to create legal certainty, including the need for more specific regulations and transparent procedures. This research is expected to contribute to the development of better policies and practices in dealing with human smuggling cases and protecting the rights of refugees in Indonesia.